Dimethylamine in cloud water: a case study over the northwest Atlantic Ocean. Issue 6 (20th October 2022) - Corral, Andrea F.; Choi, Yonghoon; Collister, Brian L.; Crosbie, Ewan; Dadashazar, Hossein; DiGangi, Joshua P.; Diskin, Glenn S.; Fenn, Marta; Kirschler, Simon; Moore, Richard H.; Nowak, John B.; Shook, Michael A.; et al.
Abstract : This study analyzes characteristics of an important alkyl amine species, dimethylamine (DMA), in cloud water over the northwest Atlantic. Abstract : This study analyzes characteristics of an important alkyl amine species, dimethylamine (DMA), in cloud water over the northwest Atlantic. Data were gathered from the winter and summer 2020 deployments of the Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment (ACTIVATE) on board the HU-25 Falcon. Thirty-eight out of 98 samples exhibited DMA above detection limits, with the overwhelming majority in the winter season (33, 52% of winter samples) compared to summer (5, 14% of summer samples). Higher levels of DMA were observed in the winter, especially during cold air outbreaks (CAOs), which was also the case for NO3 −, NH4 +, and non sea salt-SO4 2− . This is in part due to a combination of low temperatures and offshore flow enhanced with continental pollutants such as from agriculture, industry, urban activity, and biomass burning. Unlike the inorganic acidic anions, oxalate was significantly correlated to DMA in summer and the winter in both CAO and non-CAO conditions, with a presumed reason being biomass burning supported by the consistent correlation between DMA and nss-K + in each season. ACTIVATE data are compared to a cloud water dataset from the northeast Pacific, with the latter exhibiting much higher DMA levels due possibly to more abundant ocean biological emissions. The seasonal differences and enhancement in DMA during CAO conditions relative to non-CAO winter days motivates continued research into the partitioning behavior of DMA and its sources as amines play an important role in carbon and nitrogen cycles in the marine environment.